Information needs, seeking behaviour and use for sustainable development by market women in Lagos state, Nigeria (2009)
This study investigated the information needs, seeking behaviour and the sources used by market women in Lagos State for development. Random sampling method was used to select 120 market women from a population of 1200 while data was collected using questionnaire and interview methods. The women needed information mostly on finance, health and economic aspects and sought information primarily from informal sources such as friends, and colleagues, in the two markets (40%) covered to improve their welbeing. Friends, colleagues, radio and television were used daily for sourcing information. Over 87% of the respondents in both markets agreed that language of information source was the major barrier to their use of various sources. The needs of these women could be met through repackaging of information from information centres tailored to suit their needs and improve their life and society.